Five new species of Phalangopsis Serville, 1831 (Orthoptera: Phalangopsidae) from Brazilian caves in the Amazon Forest - Junta, Vitor Gabriel Pereira; Castro-Souza, Rodrigo Antônio; Ferreira, Rodrigo Lopes (Zootaxa, 2020)
The current work presents the description of five new cricket species for the genus Phalangopsis Serville, 1831 found in Brazilian caves in the Amazonas, Mato Grosso and Pará states, northern Brazil. The morphology of the phallic complex was used as the main criterion for distinguishing the species. In addition, we present data on the natural history and ecology of the new species as well as hypothesis about the variations of tegmina size in relation to the subterranean lifestyle for the genus. Finally, we provide a pictorial key based on adult males for the Phalangopsis species.